2008
DOI: 10.1073/pnas.0807054105
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of partial lexical activation

Abstract: As a spoken word unfolds over time, it is temporarily consistent with the acoustic forms of multiple words. Previous behavioral research has shown that, in the face of temporary ambiguity about how a word will end, multiple candidate words are briefly activated. Here, we provide neural imaging evidence that lexical candidates only temporarily consistent with the input activate perceptually based semantic representations. An artificial lexicon and novel visual environment were used to target human MT/V5 and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…Similar phenomena have been observed in the context of visual motion processing (e.g., Pirog et al, 2008; Dils and Boroditsky, 2010; but see Pavan and Baggio, 2010), color processing (e.g., Simmons et al, 2007), visual form processing (e.g. Zwaan et al, 2002; but see Rommers, Meyer, and Huettig 2013), gustatory processing (Simmons et al, 2013), and auditory processing (Kiefer et al, 2008)—and similar considerations apply as to whether the phenomena reflect the format of conceptual representations or rather the processing dynamics that obtain between amodal symbolic representations and input/output systems.…”
Section: Some Major Themes From This Volume and Their Broader Implicasupporting
confidence: 81%
“…Similar phenomena have been observed in the context of visual motion processing (e.g., Pirog et al, 2008; Dils and Boroditsky, 2010; but see Pavan and Baggio, 2010), color processing (e.g., Simmons et al, 2007), visual form processing (e.g. Zwaan et al, 2002; but see Rommers, Meyer, and Huettig 2013), gustatory processing (Simmons et al, 2013), and auditory processing (Kiefer et al, 2008)—and similar considerations apply as to whether the phenomena reflect the format of conceptual representations or rather the processing dynamics that obtain between amodal symbolic representations and input/output systems.…”
Section: Some Major Themes From This Volume and Their Broader Implicasupporting
confidence: 81%
“…A number of fMRI studies have reported significant engagement of this region during the processing of action verbs and sentences, compared to various baseline conditions (verbs: Damasio et al, 2001; Grossman et al, 2002; Kable et al, 2002, 2005; Noppeney et al, 2005; Tranel et al, 2005; Bedny et al, 2008; Kemmerer et al, 2008; Pirog Revill et al, 2008; Pulvermüller et al, 2009; sentences: Tettamanti et al, 2005; Wallentin et al, 2005; Chen et al, 2008; Tyler et al, 2008; Deen & McCarthy, 2010; Saygin et al, in press). These findings are often interpreted as evidence that the left pMTG—together with the left posterior superior temporal sulcus (pSTS), which was also included in our lesion maps—subserves the visual manner-of-motion features of action concepts.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, semantic conditions involving automatic processing might draw upon paradigms like lexical decision (e.g., “Is trudge a real word of English?”) and masked repetition priming (i.e., a technique that probes semantic access in a way that is completely subliminal yet also detectable with both fMRI and ERPs; see Naccache & Dehaene [2001]). For other novel approaches to distinguishing between automatic semantic processing and strategic imagery generation, see Hauk et al (2008a) and Pirog Revill et al (2008).…”
Section: Hypothesis 1: Root-level Motor Features Of Verb Meaning Amentioning
confidence: 99%
“…While investigating possible relations between mirror neurons and verb meanings in the left parietal cortex is beyond the purview of this paper, it is clearly an important direction for future research (e.g., see Glenberg & Gallese, submitted, for a new theoretical proposal about the role of action-related frontoparietal circuits in sentence processing). In addition, our hypotheses do not encompass the posterolateral temporal cortex, despite the fact that this region plays a major role, albeit predominantly in the right hemisphere, in biological motion perception (for a review see Blake & Shiffrar, 2007) and has also been implicated, albeit predominantly in the left hemisphere, in the semantic processing of action verbs (e.g., Kable et al, 2002, 2005; Noppeney et al, 2005; Kemmerer et al, 2008; Tranel et al, 2008; Pirog Revill et al, 2008; see also relevant data on thematic roles and event structure provided by, e.g., Wu et al, 2007; Grewe et al, 2007; Bedny et al, in press). We would like to emphasize, however, that even though we do not discuss the posterolateral temporal cortex in detail, we nevertheless refer, at several points in our presentation, to findings about this region that are especially pertinent to our arguments (see in particular sections 3.2.2.1 and 4.2.2.2).…”
Section: Introductionmentioning
confidence: 97%